2021
DOI: 10.5194/aab-64-53-2021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of fat deposition: <i>IL-6</i> is a hub gene in fat lipolysis, comparing thin-tailed with fat-tailed sheep breeds

Abstract: Abstract. Tail fat content affects meat quality and varies significantly among different breeds of sheep. Ghezel (fat-tailed) and Zel (thin-tailed) are two important Iranian local sheep breeds with different patterns of fat storage. The current study presents the transcriptome characterization of tail fat using RNA sequencing in order to get a better comprehension of the molecular mechanism of lipid storage in the two mentioned sheep breeds. Seven (Zel = 4 and Ghezel = 3) 7-month-old male lambs were used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…First, to compare the identified DAS genes with the reported DEGs in the previous cohort studies, a comprehensive literature review was performed. It is of interest to note that 50 DAS genes were reported as DEGs in these studies 6 , 7 , 9 11 , 16 . These genes are listed in Supplementary File S5 .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…First, to compare the identified DAS genes with the reported DEGs in the previous cohort studies, a comprehensive literature review was performed. It is of interest to note that 50 DAS genes were reported as DEGs in these studies 6 , 7 , 9 11 , 16 . These genes are listed in Supplementary File S5 .…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies have shown that AS is more frequent and complex than initially thought, and AS is likely to be involved in shaping the variations among species and breeds. Previous studies have mainly focused on the transcriptional level to explore the genetic mechanisms behind the fat-tail formation in sheep 6 , 7 , 9 11 , 16 , leaving the other important post-transcriptional regulation mechanisms, such as AS, that may also contribute to the evolution of biological complexity and phenotypic diversity in sheep fat-tail. Here, taking advantage of RNA-Seq method, a large number of samples related to seven studies, with the same purpose, were applied to elucidate the potential roles of AS regulation in forming the fat-tail of sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation prompted us to investigate further by differentiating these cells into adipocytes. Intriguingly, in fructose-treated mouse fibroblasts, there was a remarkable increase in IL6, a well-known cytokine that stimulates lipolysis 5860 . This was supported by the significant upregulation of Hsl concomitant with the increase in Cpt1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Table S2. Sheep tails from a transcriptomic perspective: mRNA profiles [4,12,14,20,21,219,[227][228][229][230][231][232][233][234][235][236][237][238][239][240][241]. Table S3.…”
Section: Supplementary Informationmentioning
confidence: 99%